Features of the use of interplanting in the cultivation of cucumber culture in light culture - V. G. Korol (Овощи России)
Relevance. Modern cultivation facilities require serious costs for their construction and subsequent operation. For the construction of 1 hectare of modern greenhouses with the cultivation of vegetable plants in light culture, about 200-250 million rubles are needed. The payback period of greenhouses is 5-6 years or more, which depends on the output from a unit area of greenhouses in value terms. And the latter, in turn, depends on the crop grown, the timing of its cultivation and receipt of products, as well as yield. Of course, the most important influence on the timing of crop cultivation and cost the resulting harvest is provided by the presence of an artificial lighting system greenhouses and its power. So expensive cultivation facilities should be used as long as possible during the year. Plan most the effective use of greenhouses throughout the year is called cultural turnover. Typically, a culture rotation includes one or more cultures. Time, one culture is called turnover. Throughout the year in each greenhouse plants are grown in one or several revolutions. And to remove or to shorten the breaks between turns on the elimination of old plants, preparation of greenhouses for a new turn and their disinfection use interplanting.Methods. The experiment was conducted in one of the greenhouses of the Moscow region in 2018 - 2019 in greenhouses equipped with artificial light of 2 hectares.Results. For various reasons, a number of greenhouse plants refuse Interplanting. Here, from our point of view, there are both objective and subjective reasons. The features of the use of interplanting when growing in light culture will be discussed in this article.